2016
DOI: 10.1016/j.eats.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Debridement of Pediatric Accessory Anterolateral Talar Facet Causing Impingement

Abstract: Symptomatic subfibular and/or lateral talocalcaneal impingement in pediatric patients may result from an accessory anterolateral talar facet (AALTF). This impingement may cause pain and disability and may limit athletic performance in high-level athletes. We report the case of a 12-year-old female competitive gymnast who had refractory, lateral-sided right ankle pain for 4 months and underwent right ankle arthroscopic resection of the AALTF causing impingement. Standard medial and anterolateral portals with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…5 Seven feet underwent AALTF resection. In 2016, Neumann et al 6 reported one foot treated with arthroscopic AALTF resection; however, they did not describe the presence of foot deformity in their case. To our knowledge, there is no report of AALTF impingement with TSVF.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…5 Seven feet underwent AALTF resection. In 2016, Neumann et al 6 reported one foot treated with arthroscopic AALTF resection; however, they did not describe the presence of foot deformity in their case. To our knowledge, there is no report of AALTF impingement with TSVF.…”
Section: Discussionmentioning
confidence: 95%
“…We searched the PubMed database on 20 April 2017 for all case reports of AALTF impingement and identified four such clinical reports. [3][4][5][6] In 53 previously reported feet, 39 flatfeet were included. In all, 46 of 53 feet were treated surgically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ankle arthroscopy portals can be used if the impingement is above the level of the posterior subtalar joint. 9 Lateral subtalar portals are used if the impingement is below the level of the posterior subtalar joint (e.g., after calcaneal malunion). 2 , 3 The calcaneofibular impingement makes the space between the calcaneus and lateral malleolus markedly limited, and the space is always filled up with thick fibrous tissue.…”
Section: Discussionmentioning
confidence: 99%